“She writes like a Woman”: Paratextual Marketing in Delarivier Manley’s Early Career - Jasper Schelstraete (Authorship, 2016)
Delarivier Manley has long been discussed as a sensational and successful Tory political satirist of the early eighteenth century. In the late seventeenth century, however, she associated with Whigs, experimented with genres, and tested different techniques for marketing her texts. Mimicking the methods of celebrity actresses, Manley used paratextual addresses to engage public interest in a carefully curated identity, creating a commodity in her persona that she would employ throughout her career. This paper traces her developing persona in her first three publications: Letters Writen by Mrs. Manley, The Lost Lover, and The Royal Mischief. Although these texts are not explicitly political satire, they nevertheless explicate the preliminary and halting machinations of an astute businesswoman and the marketing tactics Manley would employ throughout her career. The result is a more complete and nuanced picture of Manley’s commercial authorship.